2017
DOI: 10.1016/j.still.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Cover cropping and no-tillage improve soil health in an arid irrigated cropping system in California’s San Joaquin Valley, USA

Abstract: 4The impact on soil health of long-term no-tillage (NT) and cover cropping (CC) practices, alone 5 and in combination, was measured and compared with standard tillage (ST) with and without 6 cover crops (NO) in irrigated row crops after 15 years of management in the San Joaquin Valley 7 (SJV) CA, USA. Soil aggregation, rates of water infiltration, content of carbon, nitrogen, water 8 extractable organic carbon (WEOC) and organic nitrogen (WEON), residue cover, and 9 biological activity were all increased by N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
85
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(116 citation statements)
references
References 53 publications
17
85
2
3
Order By: Relevance
“…This is in accordance with many studies which have demonstrated the beneficial effects of cover crop on soil fertility and quality (e.g. Abdollahi and Munkholm, 2014;Mazzoncini et al, 2011;Mitchell et al, 2017;Sainju et al, 2002;Sapkota et al, 2012). The average annual soil organic C stock change observed in our simulations (from 0.02 to 0.28 t/ha) was similar to what has been reported by Poeplau and Don (2015) based on an extensive meta-analysis of cover crop field experiments.…”
Section: Consequences For Soil Fertilitysupporting
confidence: 92%
“…This is in accordance with many studies which have demonstrated the beneficial effects of cover crop on soil fertility and quality (e.g. Abdollahi and Munkholm, 2014;Mazzoncini et al, 2011;Mitchell et al, 2017;Sainju et al, 2002;Sapkota et al, 2012). The average annual soil organic C stock change observed in our simulations (from 0.02 to 0.28 t/ha) was similar to what has been reported by Poeplau and Don (2015) based on an extensive meta-analysis of cover crop field experiments.…”
Section: Consequences For Soil Fertilitysupporting
confidence: 92%
“…Comparisons between long‐term tillage studies utilizing the SHC are problematic because a previous version of the equation (Haney, 2015) was used in work published by Mitchell et al (2017) and Roper et al (2017), while an updated, authoritative SHC has recently become available (Haney et al, 2018). Previously a score above 7 was considered “good” (Haney, 2015), though the current recommendation is to focus on tracking the progress of individual soils over time because efficient crop production can be achieved even on soils with low SHC (Haney et al, 2018).…”
mentioning
confidence: 99%
“…In a California study, the Haney and Solvita indicators were able to differentiate among 15‐yr tillage and cover crop treatments (Mitchell et al, 2017). A long‐term field study in Michigan determined C mineralization (as estimated by Solvita 24‐h CO 2 evolution) was influenced more by crop rotation than by management system, and was more highly correlated with grain yields than were other measures of labile C and N (Culman et al, 2013).…”
mentioning
confidence: 99%
“…According to Strudley et al [79], cover crops in combination with no-tillage further improves the soil structure, and the soil integrity and number of biological pores increased, which ultimately upgrades the soil's hydraulic behavior [80]. Mitchell et al [81] observed a faster infiltration of applied water in the no-tillage and cover crops system compared to the tillage and cover crops system. Edwards et al [82] studied the increased infiltration of water via macropores created by earthworms, which could maintain the continuity of soil pores in the different horizons in the no-tillage and cover crops system [83].…”
Section: Discussionmentioning
confidence: 99%